The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/polym15224454
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Cotton Fabric/Phenolic Resin Laminated Composites Reinforced with Two-Dimensional Materials

Yonggang Guo,
Chenyang Fang,
Tingmei Wang
et al.

Abstract: In this study, cotton fabric-reinforced phenolic resin (CPF) composites were modified by adding four two-dimensional fillers: graphitic carbon nitride (g-C3N4), graphite (Gr), molybdenum disulfide (MoS2), and hexagonal boron nitride (h-BN). The tribological properties of these modified materials were investigated under dry friction and water lubrication conditions. The CPF/Gr composite exhibits significantly better tribological performance than the other three filler-modified CPF composites under dry friction,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Liu et al [ 15 ] found that MoS 2 can effectively reduce the deformation of the PI wear surface, thus reducing and stabilizing friction. Guo et al [ 16 ] doped phenolic resin (CPF) composites with 10 wt.% MoS 2 , which resulted in a 56% decrease in wear rate compared to pure CPF. The above studies show that MoS 2 -modified polymer composites have great strength and toughness, a low coefficient of friction, and high wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 15 ] found that MoS 2 can effectively reduce the deformation of the PI wear surface, thus reducing and stabilizing friction. Guo et al [ 16 ] doped phenolic resin (CPF) composites with 10 wt.% MoS 2 , which resulted in a 56% decrease in wear rate compared to pure CPF. The above studies show that MoS 2 -modified polymer composites have great strength and toughness, a low coefficient of friction, and high wear resistance.…”
Section: Introductionmentioning
confidence: 99%